Ambient Air Quality in Aurangabad - Patil, C.S.; Biradar, B.S. (Asian Journal of Chemistry, 2010)
Aurangabad is a commercial hub of the state of Maharashtra on account of its flourishing trade and commerce. Therefore, it is necessary as well as essential to assess the quality of air in selected areas.